Cultural diversity and growth of international firms - Francisco, F.R.R.; Kovalenko, O.; Kovalenko, S. (Економічний вісник Донбасу, 2016)
This article deals with the impact of national cultures on growth of international firms. It critically reviews the major contributions of the literature on this field. Starting from the seminal work of Hofstede we conclude that due to the continuous growth of globalization and the tremendous social changes, old theories such as Hofstede’s (1984) study could not be fully applicable in today’s societies. Thus, these studies should be continuously updated and the need for further research is mandatory in this field.